Unexpected inflation and cyclic impacts of policy tools on key economic variables – revealed by the assessment ratio. Issue 4 (10th May 2019) - He, Ling T.
Abstract : Purpose: The purpose of this paper is twofold, first, to develop an effective tool to assess the performance of the overall economy by creating an assessment ratio that reflects the two top priorities of monetary policy, promoting economic growth and maintaining price stability, and second, to use the annual assessment ratios to build two subsamples, outperformance (better than the historical average) and underperformance, to examine and compare the changes in impacts of monetary and fiscal policy tools on important economic variables in different economic conditions, instead of different time periods. Design/methodology/approach: The assessment ratio is defined as the gross domestic product (GDP) gap/standard deviation of inflation. Essentially, this Growth/Volatility ratio quantifies the price volatility-adjusted long-term output growth, that is, the long-term output growth given 1 per cent of the standard deviation of inflation. The growth has a positive impact on the ratio, while the effect of price volatility is negative. The ratio reflects not only the Fed's dual goal but also the fundamental economic conditions. A higher value of the ratio indicates that the economy can better handle inflation risk in driving the long-term output growth. As the inflation level is adjusted in the numerator (GDP gap), not the denominator, no matter the Fed is engaging in the fight against inflation, or for reflation (promoting inflation) to prevent deflation and pursue price stability (Bernanke, 2002), the ratio remains consistent with the Fed's dual goal and prefers a higher value. Findings: Results of this study suggest that impacts of monetary and fiscal policy tools on key economic variables may be cyclic as the economic condition changes. The policy tools can significantly affect inflation volatility and the price volatility-adjusted long-term real output growth in the subpar economic conditions identified with lower assessment ratios. The effects become insignificant when the general economic performance exceeds the historical average. More importantly, results of this study indicate that the funds rate can effectively lower the price volatility, while the fiscal tools can promote long-term real output growth in the subpar economic conditions. Therefore, when inflation volatility spikes and the real output growth slows, the decisive and timely monetary and fiscal policy decisions become necessary to enhance policy effectiveness. Originality/value: The assessments of effectiveness of monetary policy in the literature are based on some or all of four descriptive statistics: inflation, inflation volatility, output growth, and growth volatility. Each of them measures only one aspect of an economic phenomenon and cannot reflect the well-known conflicting relationship between maintaining price stability and promoting economic growth. For instance, from the policy perspective, a higher price volatility combined with a higher GDP growth rate for one period may or may not outperform another period with lower price volatility and growth rate. However, the assessment ratio created in this study considers both price volatility and economic growth simultaneously and can, therefore, be used as an effective measure of the overall economic performance.